An evaluation of financial performance of cooperatives in Malaysia : case study of Teluk Intan and Universiti Teknologi Malaysia cooperatives - Ismail, Kamariah (1991)
In this study, the history of cooperative movement in the world in general and in Malaysia in particular is considered. The study also looked at the involvement of the Malaysian government through the Cooperative Development Department, the Cooperative Apex Organization - ANGKASA, and the Cooperative coilege Malaysia. In addition, in this study an analysis of the financial performance of two cooperative societies is presented through the calculations of different performance ratios.